Lernziel Ökonomisierung? - Eine computerlinguistische Analyse der Lehrpläne zur ökonomischen Bildung an allgemeinbildenden Schulen aller Bundesländer in Deutschland - Macha, Klaas [Verfasser] (My University, 2019)
„Die Ökonomisierung aller Lebensbereiche ist eine der häufig gelesenen Schlagwortkombinationen der heutigen Zeit. Ökonomische Prinzipien, ökonomisches Denken, das Ökonomische „an sich“ durchdringe in zunehmendem Maße alle Lebensbereiche und eben auch solche, wo es nach Meinung vieler nicht hingehört, ist eine durchaus häufige Position in öffentlichen und universitären Debatten. Der vorliegende Beitrag widmet sich der Frage, inwieweit dies für Lehrpläne im Bereich der ökonomischen Bildung in Deutschland zutrifft. Um dieses Forschungsdesiderat auf einer empirischen Basis zu beheben, wurden die Lehrpläne des Themenkomplexes „Wirtschaft“ in allen allgemeinbildenden Schulen in allen Bundesländern zusammengetragen (N=140). Diese Sammlung wurde als linguistisches Corpus behandelt und mittels Methoden der Computerlinguistik analysiert. Im Ergebnis zeigte sich, dass der Wirtschaftsunterricht in Deutschland an allgemeinbildenden Schulen zuvorderst der Berufsvorbereitung dienen soll. Originär wirtschaftliche Inhalte kommen dagegen erst an dritter Stelle nach politischen Inhalten.“ (Autorenreferat; BIBB-Doku)

“The control of the structured school system in Germany requires specific curricula, which serve to pre-structure the respective lesson contents, to be split into small elements. Avenarius et al. (2003) assume that Germany is the country with the largest number of mandatory curriculums worldwide. As responsibility for the education system rests with the federal states, they are in principle free to design the curriculum. As far as the domain “economics” is concerned, this results in the well-known finding that in almost all federal states, economic contents are taught as part of different subject combinations (e.g. “economics and law” in Bavaria, “economics – orientation to career and university studies” in Baden-Württemberg or “economics/politics” in Schleswig-Holstein). However, what economic or other contents are exactly taught in these subject combinations, and to what extent, is unknown so far. To address this research desideratum, the curricula of the subjects dealing with “economics” at school were compiled of all general education schools across all German federal states (N = 116). This compilation was treated as a linguistic corpus and analysed using methods of computer linguistics. To this end, the curricula were examined for the number of citations of appropriate terms for the different content areas. It was found that the subject “economics” at general education schools in Germany mainly serves the vocational preparation of students. Economic contents in the original sense, however, only rank third after political contents.” (author’s abstract; BIBB-Doku)
How is the subject “economics” taught in Germany? : A computer linguistic analysis of pertinent curricula at general education schools of all German federal states
Keywords: S 1.1 Allgemeinbildende Schule; S 2.2.3.2 Lehrpläne; 370; Allgemeinbildende Schule; Lehrplan; Wirtschaftslehre; Ökonomische Bildung; Ökonomisierung; Berufsorientierung